Perhitungan dan Pelaporan Pajak Pertambahan Nilai (PPN) Pada PT. Mitra Tunas Raya Kabupaten Jember dengan Adanya Perubahan UU. Nomor 7 Tahun 2021 - Rafsanjani, Sofia Dwi; Susanto, Andri Mardi; Lestari, Hari Budi (Program Studi Akuntansi Fakultas Ekonomi Universitas PGRI Argopuro Jember, 2023)
This research aims to explain the calculation and reporting of value added tax at PT. Partners with Tunas Raya Jember Regency in 2022 with Law no. 7 of 2021. The research method used in this research uses a qualitative descriptive approach. Data collection techniques in this report were obtained from observations on report objects, documentation and literature studies. The results of the research show that the calculation of Value Added Tax of PT. Mitra Bersama Tunas Raya is in accordance with Law no. 42 of 2009 and Law no. 7 of 2021.